Classroom management & assessment - Slavin, Robert E.; Tate, Marcia L. (Thousand Oaks, California : Corwin Press, a SAGE Company, 2014)
If your goal is a smoother-running, participatory classroom and improved student achievement, you'll find essential best practices in this new resource, edited by a reowned education scholar, Robert E. Slavin. Dr. Robert E. Slavin, professor at John Hopkins University and the University of York, has gathered insights and findings from leading education researchers, presented in 27 succinct chapters focused on key aspects of teaching and classroom management practice. -- from back cover.
Assessment in a differentiated classroom / Carol Ann Tomlinson and Tonya Moon -- Formative assessments in high schools / Douglas Fisher and Nancy Frey -- Formative assessment and feedback to learners / Steve Higgins -- Multiple measures in classroom assessment / Susan Brookhart -- Promoting learning and achievement through self-assessment / Heidi Andrade -- Exposing the imbalance in'balanced assessment' / W. James Popham -- Do we need an assessment overhaul? / Jay McTighe and Grant Wiggins -- Formative assessment: an enabler of learning / Margaret Heritage -- Upgrading high-stakes assessments / Albert Oosterhof -- England versus Wales: education performance and accountability / Sandra McNally -- In search of feasible fidelity / David Andrews -- Before choosing, ask three questions / Steve Fleischman -- What works in classroom management / Thomas Kratochwill, Rachel DeRoos, and Samantha Blair -- Good instruction is good classroom management / Robert Slavin -- Am I the only one struggling with classroom management? / Inge Poole and Carolyn Evertson -- Classroom management: what teachers should know / Regina Oliver -- From tourists to citizens / H. Jerome Freiberg -- Promoting engagement with check and connect / Angie Pohl and Karen Storm -- Dealing with classroom management problems / Saul Axelrod -- Support for teachers around the world / Judy Hutchings -- Positive behavioral interventions and supports / Catherine Bradshaw -- First step to success for preschool children / Edward Feil, Andy Frey, and Annemieke Golly -- Improving teaching in science and mathematics / Claudia Fischer and Karen Rieck -- Improving reading and math achievement across a whole district / Allen Thurston, Peter Tymms, Christine Merrell, and Nora Conlin -- Co-teaching: inclusion and increased student achievement / Marilyn Friend and Tammy Barron -- Implementing response to instruction and intervention with older students / Nancy Frey and Douglas Fisher -- Teaching English language learners in inclusion settings / Kristi Santi and David Francis.
'Proven Programs in Education is a series of books that draws on the best of the magazine Better: Evidence-Based Education'--Publisher.
Includes bibliographical references and index.
Keywords: Classroom management -- Case studies; Educational tests and measurements -- Case studies